THE SELECTION OF MOISTURIZER FOR TREATMENT OF ATOPIC DERMATITIS - Betsy Yosia Nadeak; I Made Birawan (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2022)
Atopic Dermatitis (AD) is a chronic inflammatory skin disease that is followed by itching, and affects certain part of a body, especially in the face of  infants (infantile phase) and flexural extremities part (in childhood). The etiology of AD is multifactorial such as skin barrier defects, genetics, immune dysregulation, and environment. Atopic Dermatitis management includes skincare and prevention of recurrence. Moisturizers have been shown have an important role in preventing inflammation of the skin, repairing the skin barrier, and also routine use of moisturizer can reduce the amount of topical corticosteroids used. Currently, the use of moisturizers is one of the standard treatments in AD. This paper will explain the role and formulation of moisturizers so that it can help health workers in determining the choice of moisturizer in AD.